SOCIAL ECONOMIC FACTORS AFFECTING THE TECHNICAL INEFFICIENCY OF SHALLOTS IN MALANG DISTRICT - Sri Hindarti; Arief Joko Saputro; Lia Rohmatul Maula (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The trend of the need for shallots in Indonesia from year to year for consumption increased during 2005-2018. The increasing demand for shallots every year requires efforts to increase production quantity to meet the needs of shallots and reduce the number of imports. On average, onion farmers have not achieved efficient farming, so their farming is not optimal in increasing the amount and value of income which is heavily influenced by socioeconomic factors of farmers. The purpose of this study is to analyze technical efficiency and analyze socioeconomic factors that affect the technical inefficiency of shallot farmers. The method used is the DEA VRS Efficiency Model and Tobit regression analysis. The results show that the average technical efficiency of shallot farmers is total technical efficiency (TE CRS) 0.700, pure technical efficiency (TE VRS) 0.837, and scale efficiency 0.830. Factors influencing the technical inefficiency of shallot farmers in Malang district include land area, farmer groups, farming experience, and farmers' income.